1992
DOI: 10.1103/physrevd.45.1355
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interaction and scattering of vortices in the Abelian Higgs (or Ginzburg-Landau) model

Abstract: Line vortices arising in the Ginzburg-Landau or Abelian Higgs model are studied numerically. For a wide range of parameters simulations of parallel line vortices and antivortices were performed and the results are reported. The head-on 90" scattering is demonstrated to be independent of initial conditions provided that the vortex zeros first completely overlap. For critically coupled vortices the scattering behavior seems to be approximately velocity independent until P-0.4 and the collisions are approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 17 publications
11
70
0
Order By: Relevance
“…This is e.g. supported by twodimensional simulations of vortex collisions, where it has been shown that colliding vortices only overlap above a critical velocity [52]. We expect typical velocities to be indeed small in our scenario due to the large number density of mutually repelling flux tubes formed during the phase transition, as discussed above.…”
Section: Network Decay and Reheatingsupporting
confidence: 63%
“…This is e.g. supported by twodimensional simulations of vortex collisions, where it has been shown that colliding vortices only overlap above a critical velocity [52]. We expect typical velocities to be indeed small in our scenario due to the large number density of mutually repelling flux tubes formed during the phase transition, as discussed above.…”
Section: Network Decay and Reheatingsupporting
confidence: 63%
“…The link forms and unforms, the two strings becoming separately visible again. This is not surprising; the process is essentially right-angle scattering which is well-established by numerical experiments with vortices [25,26]. Analytically, right-angle scattering after a head-on collision is understood at critical coupling (β = 1) [27], in terms of geodesic motion in the moduli space approximation.…”
Section: Resultsmentioning
confidence: 94%
“…8 is not symmetric with respect to the vertical line passing through its maximum. As in the previous case, we also studied the evolution of the initial configuration of the type (21), solving the exact equation of motion (2) reproduces the corresponding result of Ref. [28].…”
Section: Kink Collisions In the ϕ 6 Modelmentioning
confidence: 96%
“…Special attention should be paid to configurations of strings or vortices [1, 14,15]. In particular, there are important results on quantum stabilization of strings [16][17][18] and strings/vortices/monopoles dynamics [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%